Iodine status of pregnant women from the Republic of Cyprus - Cannas, Andrea; Rayman, Margaret P; Kolokotroni, Ourania; Bath, Sarah C (My University, 2023)
Iodine supply is crucial during pregnancy to ensure the proper thyroid function of mother and baby and support fetal brain development. Little is known about iodine status or its dietary determinants in pregnant women in the Republic of Cyprus. We therefore recruited 128 pregnant women at their first-trimester ultrasound scan to a cross-sectional study. We collected spot-urine samples for the measurement of urinary iodine concentration (UIC, µg/L), and creatinine concentration (Creat, g/L), the latter of which allows us to correct for urine dilution and to compute the iodine-to-creatinine ratio (UI/Creat). Women completed a Food Frequency Questionnaire (FFQ) and a general questionnaire. We used a General Linear model to explore associations between maternal and dietary characteristics with UI/Creat. The median UIC (105 µg/L) indicated iodine deficiency according to the World Health Organisation criterion (threshold for adequacy=150 µg/L) and the UI/Creat was also low at 107 µg/g. Only 32% (n=45) of women reported the use of iodine-containing supplements; users had a higher UI/Creat than non-users (131 µg/g vs. 118 µg/g), though this difference was not significant in the adjusted analysis (P=0.37). Of the dietary components, only egg intake was significantly associated with a higher UI/Creat in adjusted analyses (P=0.018); there was no significant association with milk, dairy products, or fish intake. Our results suggest that pregnant women in Cyprus have inadequate iodine status and are at risk of mild-to-moderate iodine deficiency. Further research on dietary sources in this population is required.
Keywords: Iodine; Iodine deficiency; Iodine intake; Iodine status; Pregnancy; Republic of Cyprus; Supplement